Assessment Functional and its Practice in Applied Contexts (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The current manuscript goes through the literature in an unsystematic way to describe the functional assessment process within the analytical-behavioral approach and can be characterized as a support reading for behavior analysts who work with the application. Initially, the text is developed presenting the empirical basis of the functional assessment process. It continues with the focus on the functional assessment process with an experimental status. It provides the methods of the functional assessment process: functional assessment by indirect observation, functional assessment by direct observation, and functional analysis. Emphasis is given to the manipulation of variables - or functional analysis - as an experimental strategy used to demonstrate functional relationships, and whose development has reached a high degree of precision in identifying the sources of reinforcement of the problem behavior. In conclusion, the methods of assessment and functional analysis should be considered mandatory for the application of behavioral interventions to modify severe problem behaviors.
Keywords: severe problem behaviors; functional assessment; functional relationship; behavior modification